(untitled) (Texas Journal of Engineering and Technology, 2023)
Optimizing cutting operations to minimize costs has become crucial in the competitive manufacturing industry. This study combines experimental and analytical modeling to understand the dynamic properties of machine tool spindle and cutting tool assembly. By characterizing the system and employing finite element analysis, the research aims to enhance cutting tool development, process planning, and productivity while minimizing dynamic testing. The focus is on achieving stability, reliability, and efficiency in cutting operations.